5. Identification and Distribution of Carbohydrates on Sex Accessories Glands of Male Aceh Cattle - Muhammad Jalaluddin; Mustafa Sabri; Herlina Yuliani; Fadli A. Gani; Hamny Hamny; Sri Wahyuni (Jurnal Medika Veterinaria, 2019)
This study aimed to determine the content and distribution of carbohydrate in the sex accessory glands of Aceh cattle. The sex accessory glands of Aceh cattle that were used consisted of a vesicular gland, prostate gland and bulbourethral gland. The entire gland was processed into histological preparation. The content of neutral carbohydrate distribution was observed with periodic acid Schiff (PAS) staining while acid carbohydrates using alcian blue (AB) staining pH 2,5. The results showed that the content and distribution patterns of carbohydrate acid and neutral carbohydrate were different on every sex accessory glands of Aceh cattle. The content of acid-carbohydrate with the intensity of reaction with moderate (++) to strong (+++) intensity was found on the prostate gland and bulbourethral gland. Meanwhile, the neutral carbohydrate with low intensity (+) was found in the vesicular gland, prostate gland and bulbourethral gland. The content of acid carbohydrate was scattered throughout the prostate gland and bulbourethral gland of Aceh cattle, a carbohydrate with high concentrations (+++) was found in the bulbourethral gland.